2019
DOI: 10.1186/s13690-019-0342-4
|View full text |Cite
|
Sign up to set email alerts
|

Nothing about me without me: why an EU health literacy strategy embracing the role of citizens and patients is needed

Abstract: As a multi-faceted concept, health literacy concerns the capacities of people to meet the complex demands of health in a modern society, starting with basic skills and ending with active citizenship. The importance of advancing health literacy in Europe was recognised by the European Commission in various communications and initiatives and most recently by the OECD. However, a strategic approach combined with a long-term action plan is still missing. This commentary advocates for an EU strategy on health liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…To calculate the score of the HLS-EU-Q16, the answers were dichotomised into two categories with two scores-easy (easy or very easy) and difficult (difficult or very difficult). The HL score is a sum score and three levels have been defined-inadequate HL (0-8), problematic HL (9)(10)(11)(12) and adequate HL (13)(14)(15)(16). The categories were dichotomised into adequate and not adequate (inadequate and problematic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the score of the HLS-EU-Q16, the answers were dichotomised into two categories with two scores-easy (easy or very easy) and difficult (difficult or very difficult). The HL score is a sum score and three levels have been defined-inadequate HL (0-8), problematic HL (9)(10)(11)(12) and adequate HL (13)(14)(15)(16). The categories were dichotomised into adequate and not adequate (inadequate and problematic).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HL provides the capability to change one's beliefs if necessary [6]. Conversely, limited HL is an increasing problem affecting the general population [7][8][9][10][11][12][13][14][15]. A low level of HL leads to the misuse of available health resources and inappropriate access to care, which is defined as the degree of adaptation between patient skills and health-care system requirements [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Given its health effects, several European Union (EU) initiatives address HL: in 2007, HL was identified as a policy priority in the European Commission's health strategy "Together for Health 2007-2013" 8 ; in 2012, improving HL was included among the priorities of the Health 2020 strategy of the World Health Organization (WHO) Regional Office for Europe 9 ; and in 2014, the first comparative survey on population literacy across eight EU countries was conducted 10 . At the international level, the WHO included HL as one of the key health promotion pillars needed for a successful 2030 Agenda for Sustainable Development 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the number of published studies on HL has steadily increased and it is now considered as one of the main determinants of health and healthcare service use [ 2 ]. At present, low levels of HL are quite common: for instance, the results of the first European Health Literacy Survey (HLS-EU), conducted in 2011 in eight European Countries, showed that about 47% of respondents reported limited HL skills [ 3 ].…”
Section: Introductionmentioning
confidence: 99%